Mobile user interface design based on eye-tracking and users' mental model patterns / Aslina Baharum ... [et al.] - Baharum, Aslina; Mat Zain, Nurul Hidayah; Mohd. Rusli, Nordaliela; Ramli, Ratna Zuarni; Halamy, Suhaida (Division of Research and Industry Linkages, 2017)
In recent years, the emergence of smartphones has changed the definition of mobile phones. It has become an essential part of the peoples’ communication and daily life. Mobile application have become more popular nowadays with the emergence of smartphones, especially for online shopping. Women and men have different perspectives in most activities including shopping. Recently, online shopping has grown in their popularity in line with growing of the Internet and shopping mobile apps on smartphones. Mobile apps are designed and developed by developers and are available in app stores. Mobile user interface (Ul) design is an essential in the mobile apps development process. A poor user interaction with mobile apps could lead to failure of apps. Most of the previous research is improving general Ul such as graphical icons, multi-layered interfaces and augmenting the mobile interface approach. User Interface Design is a crucial part of mobile app development and mental model theory does help developers in designing more users friendly and strong visual hierarchy user interface for mobile apps. Mix method will be used throughout this research using ‘Localization’ to obtain the users’ Mental Model pattern based on users’ expectation. Moreover, the qualitative and quantitative data will be collected through eye-tracking technology. Mental model theory can help the mobile apps developers to design a greater Ul. This study will explain how mental model theory is used in interface design practices for a mobile apps development. The expected outcome of the research is to develop a users' Mental Model pattern by gender as a guideline and support by analysis of eye-tracking technology towards an effective mobile app in order to satisfy the users. Therefore, a good user interaction between the user and an app increase the popularity of the mobile apps.